Inovasi Pembelajaran Cerita Anak: Pengembangan E-Komik Interaktif berbasis Multimedia - Tahir, Arifin; Tahir, Muhlis (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
An effective and fun learning process plays an important role in increasing students' interest in understanding culture, one of which is folklore, based on an initial survey at SDN Keleyan 1 the available learning media is less interesting and interactive, so that students' interest in folklore decreases by up to 60%. This research aims to develop e-comics as a learning medium for folklore for grade VI students. This type of research is development using the ADDIE model with the stages of Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques include observation and questionnaires. Data analysis was carried out in a quantitative descriptive manner to assess the feasibility and effectiveness of the product. The results of this study are in the form of e-comics which show that e-comics are very feasible with a 100% feasibility percentage based on expert assessments. Student responses to small and large group trials reached 92.38% and 90.24%, with features such as dynamic illustrations, interactive quizzes, and engaging storylines. Students' comprehension improved by an average of 35% after using e-comics.  E-comics are effective and feasible to be used as a learning medium that can increase students' interest and understanding of folklore. This media makes a theoretical contribution to the development of culture-based digital learning and is ready to be used in the classroom or independently.